Reflexiones sobre el arbitraje como mecanismo alternativo para la solución de conflictos individuales de trabajo (Tema Central) - Jara Vásquez, María Elena (2015)
Ecuador lacks experience in labor arbitration for individual conflicts. This article explores this alternative, especially from the perspective of the advantages and challenges related to the access to justice. In summary, this article support the idea that arbitration is a vehicle to make access to justice easier. However, considering the situation and vulnerability of workers, special substantive and procedural provisions are indispensable in order to avoid that arbitration becomes a barrier to those seeking access to justice.